Necesidad de la provisión de alimentos para los hijos de hasta 24 años de edad que se encuentren cursando estudios en Guaranda 2022. - Cruz Garcés, Joselyn Esther (2024)
This research work will be framed in the provision of maintenance for children up to 24 years of age who are pursuing higher education, since many research papers have been written about the right to maintenance, however, in most of these works carried out, there is not one that deals in a more specific way and with more depth in making a reform to the law and thus be able to extend the payment of alimony from 21 to 24 years of age in our country. The payment of alimony up to the age of 21 is one of the rights guaranteed by the Ecuadorian State, so this right has to be satisfied by the parents, but it turns out that one of the parents who is not living with the people he has to support, in this case has the obligation to fulfill his responsibility to contribute financially so that their children can have a dignified life, but in case they do not do so, the person who has custody of the minor children has the right to pursue legal action; However, this right has an early termination, which causes repercussions on the academic performance of a child. It is important to add that there may be several legal characteristics that make it possible to determine a legal relationship, including the relationship that must exist between the plaintiff and the defendant, such as the reciprocal obligations, rights, responsibility and type of action to be taken. Among other aspects that must be considered in order to correctly determine food extinction. In this project, materials and methods will be applied that will allow the development of the research, as well as surveys will be applied to legal professionals, the 5 results of which will serve to propose the legal reform project to the Organic Code of Children and Adolescents, with the aim of extending age up to 24 years the right to claim alimony, for those young people who are pursuing higher education in the city of Guaranda, whose modification will be made to article (129) numbered 4. KEYWORDS: Right to alimony, development, higher education, youth, alimony